BRAIN MITOCHONDRIA : II. The Relationship of Brain Mitochondria to Glycolysis - Beattie, Diana S. (The Rockefeller University Press, 1963)
A mitochondrial fraction prepared from calf brain cortex possessed negligible glycolytic activity in the absence of the enzymes of the high speed supernatant fraction. When mitochondria were added to a supernatant system supplemented with optimal amounts of crystalline hexokinase, a 20 per cent stimulation of glycolysis was observed. The supernatant fraction produced minimal amounts of lactate in the absence of exogenous hexokinase; the addition of mitochondria doubled the lactate production. The substitution of glycolytic intermediates for glucose as substrates as well as the addition of exogenous glycolytic enzymes to the supernatant fraction or supernatant fraction plus mitochondria indicated that the mitochondria contributed mainly hexokinase and phosphofructokinase. By direct assay of all of the enzymes of the glycolytic pathway, only hexokinase and phosphofructokinase were shown to be concentrated in the mitochondrial fraction. All other glycolytic enzymes were found to exhibit higher total and specific activities in the supernatant fraction.